Optical Readout of the Néel Vector in the Metallic Antiferromagnet Mn2Au - Grigorev, Vladimir; Filianina, Mariia; Bodnar, Stanislav Yu; Sobolev, Sergei; Bhattacharjee, Nilabha; Bommanaboyena, Satya; Lytvynenko, Yaryna; Skourski, Yurii; Fuchs, Dirk; Klaeui, Mathias; Jourdan, Martin; Demsar, Jure (Physical Review Applied, 2021)
Metallic antiferromagnets with broken inversion symmetry on the two sublattices, strong spin-orbit coupling, and high Néel temperatures offer alternative opportunities for applications in spintronics. Especially Mn2Au, with a high Néel temperature and high conductivity, is particularly interesting for real-world applications. Here, manipulation of the orientation of the staggered magnetization, (i.e., the Néel vector) by current pulses was recently demonstrated, with the readout limited to studies of anisotropic magnetoresistance or x-ray magnetic linear dichroism. Here we report on the in-plane reflectivity anisotropy of Mn2Au(001) films, which are Néel vector aligned in pulsed magnetic fields. In the near-infrared region, the anisotropy is approximately 0.6%, with higher reflectivity for the light polarized along the Néel vector. The observed magnetic linear dichroism is about 4 times larger than the anisotropic magnetoresistance. This suggests the dichroism in Mn2Au is a result of the strong spin-orbit interactions giving rise to anisotropy of interband optical transitions, which is in line with recent studies of electronic band structure. The considerable magnetic linear dichroism in the near-infrared region could be used for ultrafast optical readout of the Néel vector in Mn2Au.
CRIS-Team Scopus Importer:2023-03-27